x^2+y^2 = 2023
tìm x;y
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,=\dfrac{x^2-2xy+y^2}{\left(x-y\right)\left(x+y\right)}=\dfrac{\left(x-y\right)^2}{\left(x-y\right)\left(x+y\right)}=\dfrac{x-y}{x+y}\\ b,=\dfrac{x^2+2xy+y^2-x^2+2xy-y^2-4y^2}{\left(x-y\right)\left(x+y\right)}=\dfrac{4xy-4y^2}{\left(x-y\right)\left(x+y\right)}=\dfrac{4y\left(x-y\right)}{\left(x-y\right)\left(x+y\right)}=\dfrac{4y}{x+y}\)
a) \(\left(x+y\right)^2+\left(x-y\right)^2+\left(x+y\right)\left(x-y\right)\)
\(=x^2+2xy+y^2+x^2-2xy+y^2+x^2-y^2\)
\(=3x^2+y^2\)
b)\(\left(3x+y\right)^2+\left(3x-y\right)^2-\left(2x+y\right)\left(2x-y\right)\)
\(=9x^2+6xy+y^2+9x^2-6xy+y^2-4x^2+y^2\)
\(=14x^2+3y^2\)
c) \(2\left(x-y\right)\left(x+y\right)+\left(x+y\right)^2+\left(x-y\right)^2\)
\(=\left(x-y\right)^2+2\left(x-y\right)\left(x+y\right)+\left(x+y\right)^2\)
\(=\left(x-y+x+y\right)^2\)
\(=4x^2\)
d)\(-2\left(x^2-9y^2\right)+\left(x-3y\right)^2+\left(x+3y\right)^2\)
\(=\left(x+3y\right)^2-2\left(x+3y\right)\left(x-3y\right)+\left(x-3y\right)^2\)
\(=\left(x+3y-x+3y\right)^2=9y^2\)
\(a,\left(x+2\right)^2-\left(x-2\right)^2-2\left(x-2\right)\left(x+2\right).\)
\(=\left(x+2-x+2\right)^2=4^2=16\)
\(b,\left(x-y\right)^2+\left(x+y\right)^2+2\left(x-y\right)\left(x+y\right)\)
\(=\left(x-y+x+y\right)^2=x^2\)
\(c,\left(x-y+z\right)^2-2\left(x+y\right)-2\left(x+y\right)\left(x-y\right)-z^2\)
\(\left(a\right):\left(x+y\right)^2-\left(x-y\right)^2=x^2+2xy+y^2-\left(x^2-2xy+y^2\right)\\ =x^2+2xy+y^2-x^2+2xy-y^2\\ =4xy\)
\(\left(b\right):\left(x-y-z\right)^2+\left(x+y+z\right)^2\\ =\left[\left(x-y\right)-z\right]^2+\left[\left(x+y\right)+z\right]^2\\ =\left(x-y\right)^2-2z\left(x-y\right)+z^2+\left(x+y\right)^2+2z\left(x+y\right)+z^2\\ =x^2-2xy+y^2-2xz+2yz+z^2+x^2+2xy+y^2+2xz+2yz+z^2\\ =2x^2+2y^2+2z^2+4yz\)
\(\left(c\right):\left(x+y\right)^2-2\left(x+y\right)\left(x-y\right)+\left(x-y\right)^2\\ =\left[\left(x+y\right)-\left(x-y\right)\right]^2\\ =\left(x+y-x+y\right)^2\\ =\left(2y\right)^2=4y^2\)
\(A=x^2-2xy+y^2+x^2+2xy+y^2+x^2-y^2=3x^2+y^2\\ B=\left(x-y-x+y-z\right)^2=\left(-z\right)^2=z^2\)
trả lời hộ mình với\